Decellularisation of porcine oesophagus - Lim, Kenneth Jun Yang (2019)
Studies have been done to find out more about how to obtain suitable oesophageal scaffolds to be used for regenerative medicine in tissue engineering. By obtaining suitable oesophageal scaffold that allows recellularisation, surgical improvements for patients with oesophageal disorders could be realised. Sodium dodecyl sulphate (SDS) is known to be effective in removing cellular components in the decellularisation process. However, due to having properties that can cause extracellular matrix (ECM) to change and also cause injurious effects to living animals and humans, it must be fully removed from the decellularised ECM scaffold before using it for transplant. This study looks into the effects of how different concentrations of propanol would affect the efficiency in the removal of SDS. Oesophagus samples would first undergo decellularisation by perfusion using SDS. A sample would then be characterised by histology to make sure all samples were fully decellularised. The remaining decellularised samples would go through a washing process using deionised (DI) water and 1% propanol to remove SDS by perfusion for 24 hours. Another study was conducted to understand if propanol could remove residual SDS from a sample. A decellularised sample went through three washing processes to remove SDS, each process lasting 24 hours, with DI water, 1% propanol and 5% propanol. Results from the first study shows DI water (0% propanol) had the best efficiency in removing SDS compared to 1% propanol. However, results from the second study shows increasing propanol concentration was effective in removing residual SDS.